Can this be evil? Evilness seen as intention or drive. Issue 2 (2nd July 2016) - Berggren, Gunnar
ABSTRACT: This article was originally read as an introductory plenary paper at the German-Nordic Clinical Conference, September 2015 in Berlin. The heading of the conference was 'On Cruelty and Destructiveness'. The paper takes as its starting point the composite figure of Dr Jekyll and Mr Hyde. It discusses the meaning of intentionality, or the lack of a conscious intention of being evil, in comparison to evil deeds caused by uninhibited drive satisfaction. Evilness is put into a social and a psycho-developmental context. Examples of contemporary atrocities are discussed, leading up to a formulation of a multi-factorial explanatory model of evil, taken from Michael Stones book 'The Anatomy of Evil'.